EFFECTS OF AUXINS AND CYTOKININS ON IN VITRO MULTIPLICATION OF BANANA (MUSA SPP.) VARIETY ‘W-11’ IN PAKISTAN - S. H. Shah1; N. Khan; S. Q. Memon; M. Latif; M. A. Zia; A. Muhammad; K. Nasir; Zafarullah (Journal of Animal and Plant Sciences, 2020)
Banana is mostly propagated by conventional method of sucker which is very slow process. Moreover, in vegetative propagation, the plants once infected by pathogen can shift it to many generations and the whole plant population may be infected within few years. In vitro propagation of banana is the best alternative approach that leads to a rapid process of propagation and also the production of disease-free plants. Therefore, the present study was conducted at Plant Tissue Culture Laboratory and Plant Sciences Laboratory, Science Complex, Allama Iqbal Open University, Islamabad, Pakistan during the year 2017. In seven different treatments, Murashige and Skoog basal media was supplemented with different concentrations of BAP and IAA. During this study, the experiments were performed using completely randomized design (CRD) with three replications. Least significant difference (LSD) test was applied to assess the significant differences among means. The results reveal that the highest number of shoots (366.6) was produced after 6th subculture. During this study, the highest proliferation rate (92.22%) was recorded in T6; MS salts supplemented with BAP (2.0 mg/l) and IAA (0.5 mg/l). The minimum number of days (6) for bud initiation was recorded in T6. Similarly, the highest average fresh weight (14.88 g) was recorded in T6. The highest number of main roots (9.25 ± 2.08) were recorded in MS basal media supplemented with IAA (2.0 mg/l) and BAP (0.5 mg/l). It was followed by MS basal media fortified with IAA (3.0 mg/l) and BAP (1.0 mg/l) that gave 7.81 ± 1.03 number of shoots. The survival rate (92%) was recorded in acclimatization when the plantlets were transferred in plastic pots having peat moss under controlled condition. This optimized protocol would be helpful for mass scale production of high yielding and disease-free banana plants in future.
Keywords: Banana Bunchy Top Virus; BAP; IAA; In vitro regeneration; MS basal media